Analisis Pengaruh Lingkungan Kerja Terhadap Kepuasan Kinerja Pegawai di RSUD I. A Moeis Samarinda - Ariyanto, Yogi; Umar, Zulkifli; Ardan, M (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2025)
This study aims to analyze the influence of the work environment on employee job satisfaction at I.A. Moeis Regional General Hospital (RSUD I.A. Moeis) Samarinda. This research is crucial because, based on a preliminary study, 4 out of 5 employees expressed dissatisfaction with their work environment, particularly amid increasing service demands. The findings of this study are expected to provide new insights into improving the quality of human resource management in the healthcare sector. The research employs a quantitative approach with a cross-sectional design. The study population consists of all 650 employees of RSUD I.A. Moeis Samarinda, with a sample size of 200 employees selected using purposive sampling techniques. Data collection was conducted through questionnaires designed to measure respondents' perceptions of the work environment and job satisfaction. The collected data were analyzed using the Spearman correlation method with the assistance of computerized software. The results indicate a significant relationship between the work environment and job satisfaction, with a p-value of 0.000. The Spearman correlation coefficient shows a positive relationship, meaning that the better the perceived work environment, the higher the level of employee job satisfaction. The conclusion of this study is that the work environment plays a crucial role in improving employee job satisfaction. Therefore, improving the work environment, such as providing adequate facilities, fostering a conducive work atmosphere, and offering managerial support, is highly recommended to enhance employee performance and well-being at RSUD I.A. Moeis Samarinda.